School safety preparedness: a survey study of K-12 principals’ perceptions relative to safe and secure Kansas public schools - Scott, Renee L. (Kansas State University, 2020)
The purpose of this quantitative research study was to explore Kansas K-12 principals perceived preparedness of school safety. To achieve this objective, a specific research question and three research hypotheses were formulated around perceived preparedness for Kansas school principals who are responsible for implementing school safety practices in Kansas public schools. A survey aligned to the Kansas Safe and Secure School Standards was utilized to assess principal perceptions. According to the findings, there were not statistically significant differences in perceptions between elementary and secondary principals or urban and rural principals pertaining to perceived safety preparedness. The findings did reveal an increased perceived preparedness when safety drills were conducted. The findings of this study provide additional insight into the level of implementation and understanding of the standards by Kansas public school principals. As practice and policy continue to evolve regarding safety drills, it is critical that a system of accountability is utilized to ensure appropriate laws and practices are in place. The findings of this study may provide information for Kansas school districts, the Kansas State Department of Education, and Kansas lawmakers as they work to improve prevention of school violence and set governing policy in schools.
Keywords: School safety; Principal preparedness; Kansas principal preparedness for school safety; School safety standards; School violence preparedness; Elementary and secondary principal preparedness; School safety drills